English Noun+Noun Syntactic Structures in English for Specific Purposes and their Serbian Equivalents - Rajović, Jelena D.; Spasić-Stojković, Milica M (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The purpose of this study is to investigate if there is a structure agreement between syntactic structures consisting of two nouns [N + N] in English for Occupational Health and Safety and their Serbian equivalents. After narrowing down the results of the research to approximately five thousand examples and ordering them by frequency of appearance in the corpus, a sample of about one hundred and seventy items was extracted and translated into Serbian. The analysis shows that there are three main types of Serbian translation equivalents but none of them are structurally identical to English noun + noun structures.
Keywords: English for specific purposes; syntactic structures; Occupational health and safety; Serbian language; English language